Association of cortical thickness and neurological soft signs in patients with chronic schizophrenia and healthy controls - Kong, Li; Herold, Christina; Lässer, Marc; Schmid, Lena A.; Hirjak, Dusan; Thomann, Philipp; Essig, Marco; Schröder, Johannes (Neuropsychobiology, 2015)
Neurological soft signs (NSS), i.e. subtle neurological abnormalities, have been frequently found in schizophrenia. Neuroimaging studies in schizophrenia have shown abnormal cortical thickness changes across the cortical mantle. However, few studies have examined relationships between NSS and cortical thickness abnormalities in schizophrenia.
Gesehen am 15.07.2020